2015
DOI: 10.1186/s12885-015-1689-8
|View full text |Cite
|
Sign up to set email alerts
|

Frequent down-regulation of ABC transporter genes in prostate cancer

Abstract: BackgroundATP-binding cassette (ABC) transporters are transmembrane proteins responsible for the efflux of a wide variety of substrates, including steroid metabolites, through the cellular membranes. For better characterization of the role of ABC transporters in prostate cancer (PCa) development, the profile of ABC transporter gene expression was analyzed in PCa and noncancerous prostate tissues (NPT).MethodsTaqMan Low Density Array (TLDA) human ABC transporter plates were used for the gene expression profilin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
48
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(51 citation statements)
references
References 30 publications
3
48
0
Order By: Relevance
“…Several identi ed genes in our results have previously been reported to play important roles in several types of cancer. Wang, Y. et al study found that the expression of ABC transporter gene (ABCA8) was signi cantly down-regulated in prostate cancer as compared to noncancerous prostate tissues [35]. This was consistent with our result that the expression level of ABCA8 was signi cantly decresed in invasive group vs. non-invasive group.…”
Section: Discussionsupporting
confidence: 92%
“…Several identi ed genes in our results have previously been reported to play important roles in several types of cancer. Wang, Y. et al study found that the expression of ABC transporter gene (ABCA8) was signi cantly down-regulated in prostate cancer as compared to noncancerous prostate tissues [35]. This was consistent with our result that the expression level of ABCA8 was signi cantly decresed in invasive group vs. non-invasive group.…”
Section: Discussionsupporting
confidence: 92%
“…Dysregulation of cholesterol homeostasis and tumor progression in human prostate cancer through cancerspe cific ABCA1 hypermethylation and loss of protein expres sion was proposed by Lee et al 30 Their results were recently confirmed by Demidenko et al, 29 who reported that the ABC gene expression profile characterized by the downregulation of several genes was particularly preva lent in the TMPRSS2-ERGnegative prostate tumors. However, although the TMPRSS2-ERG gene fusion is the most prevalent genetic rearrangement, found in All-tumor characteristics in relation to control tissues Hlavata et al 16 Colorectal A12, A13, B6, C1, C2, and E1 Mohelnikova-Duchonova et al 17 Pancreatic B4, B11, C1, C3, C5, C10, and G2 Heimerl et al 27 Melanoma cell lines B3, B6, C2, C4, E1, and F2 A7, A12, B2, B4, B5, and D1 Demidenko et al 29 Prostate approximately 50% of prostate cancers, studies examining its clinical implications have reported ambiguous results.…”
Section: Discussionmentioning
confidence: 81%
“…However, although the TMPRSS2-ERG gene fusion is the most prevalent genetic rearrangement, found in All-tumor characteristics in relation to control tissues Hlavata et al 16 Colorectal A12, A13, B6, C1, C2, and E1 Mohelnikova-Duchonova et al 17 Pancreatic B4, B11, C1, C3, C5, C10, and G2 Heimerl et al 27 Melanoma cell lines B3, B6, C2, C4, E1, and F2 A7, A12, B2, B4, B5, and D1 Demidenko et al 29 Prostate approximately 50% of prostate cancers, studies examining its clinical implications have reported ambiguous results. 31,32 Based on all the abovedescribed research findings, our team raised the question about the existence of general ABC gene expression profiles, which could be common to different tumor types, and their possible clinical implica tions.…”
Section: Discussionmentioning
confidence: 99%
“…Among the various mechanisms that are responsible for MDR, active effluxes of the chemotherapeutic drugs through ABC transporters play a major role in cancer cells in resisting chemotherapy [37]. Several studies conducted on over-expression of ATP-binding cassette transporter genes, ABCB1 (P-gp or MDR1) and ABCC1 (MRP1) were found to be responsible for chemotherapeutic drug resistance in PCa[5]. Similar observations were made in the current study where ABCB1, ABCC1, and ABCG2 were found to be overexpressed in DTX resistance cells (PC3-R) that we generated.…”
Section: Discussionmentioning
confidence: 99%
“…However, resistance to docetaxel has emerged in PCa cells, and the known mechanisms include that limit of the intracellular drug concentration [3]. Among the various studies that were conducted to uncover the potential mechanisms for the development of resistance in PCa, over-expression of several ABC transporters was found to be responsible for the efflux of chemotherapeutic drugs [5]. Thus, the development of agents able to modulate multidrug resistance (MDR) mediated by efflux pumps remained a major goal for PCa therapy.…”
Section: Introductionmentioning
confidence: 99%